Who cares and who is careless? Insufficient effort responding as a reflection of respondent personality. [article]. - Bowling, Nathan
Insufficient effort responding (IER) to surveys, which occurs when respondents fail to carefully read questionnaire instructions or item content, has recently gained attention as a source of inaccuracy in self-report data (Huang, Curran, Keeney, Poposki, & DeShon, 2012; Johnson, 2005; Maniaci & Rogge, 2014; Meade & Craig, 2012). Whereas previous studies have focused on IER as a methodological nuisance, the current studies examined IER as a substantive variable. Specifically, we hypothesized that IER is a reflection of enduring individual differences. In Study 1, we found that IER displayed rank-order consistency over the course of 13 months; in Studies 2 and 3, we found that IER displayed rank-order consistency across multiple research situations; in Study 4, we found that acquaintance-reported conscientiousness, agreeableness, extraversion, and emotional stability were each negatively related to IER; and in Study 5, we found that IER was related to college grade point average and class absences. Together, these 5 studies suggest that IER is in part a manifestation of enduring individual differences. -- (from the authors)
Keywords: Sagioglou, Christina; Insufficient effort responding; Careless responding; Response effort; Behavioral consistency; Personality